Orta Çağ'da Yaşamış iki Alman Esirin Gözünden Osmanlı-Türk Toplumunda Sosyal Değerler - Öztürk, Ali Osman (Enthalten in:Diyalog;Meram : GERDER, 2013-;(2020), Seite 18-35)
Johannes Schiltberger wrote what he lived as a prisoner in Turkey, Syria, Egypt, Iran, Central Asia, and Siberia between 1394-1427 in his book titled
10.37583/diyalog.802161